Gender Bias and the Law of Evidence: The Link Between Sexuality and Credibility - McDonald, Elisabeth (Victoria University of Wellington Law Review, 1994)
In sexual assault trials, the credibility of the complainant, or the "primary witness", will often be an issue. Prior to the enactment of section 23A of the Evidence Act 1908, which governs the admissibility of sexual history evidence, the complainant's veracity was often questioned on the basis of her prior sexual experience. Under section 23A, such sexual history evidence must be of "direct relevance" to a fact in issue to be admissible. The concept of relevance and reasonableness also governs the admissibility of "recent complaint" evidence in sexual assault trials, with varying results. This comment examines the concept of relevance in light of two Court of Appeal decisions, and discusses how the link between sexuality and credibility is still being made by New Zealand courts.